2018
DOI: 10.1016/j.neuropsychologia.2018.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Impaired theory of mind in adults with traumatic brain injury: A replication and extension of findings

Abstract: We replicated findings of lower scores in adults with TBI on a video-based ToM task, and provided additional evidence of the effect of WM load on social cognition task performance. There were no significant accuracy differences between men and women, inconsistent with prior evidence - including our own data using the same test. There is strong evidence of a female advantage on other social cognition tasks, and the parameters of this advantage remain to be discovered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 58 publications
2
20
2
Order By: Relevance
“…Turkstra (42) compared men and women with TBI to uninjured peers on a ToM test, and replicated the study in a subsequent sample (41). Participants watched brief video vignettes of social interactions and made ToM judgements about actors in the videos.…”
Section: Sex Differences In Social Cognition In Adults With Tbimentioning
confidence: 93%
See 2 more Smart Citations
“…Turkstra (42) compared men and women with TBI to uninjured peers on a ToM test, and replicated the study in a subsequent sample (41). Participants watched brief video vignettes of social interactions and made ToM judgements about actors in the videos.…”
Section: Sex Differences In Social Cognition In Adults With Tbimentioning
confidence: 93%
“…The typical experimental ToM task is a version of the classic False Belief task (38) or Piaget's (39) perspectivetaking task, in which the participant must recognize that one actor in a scenario has access to information that the other does not. Most studies have reported no significant difference on ToM tasks between men and women (37,(40)(41)(42) or girls and boys [e.g., (43)]; although some have reported trends for better scores in females [e.g., (44)]. ToM findings contrast with those on emotional empathy (feeling the feelings of others), for which women are thought to have an advantage (45).…”
Section: Sex Differences In Social Cognition In Typical Adultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another limitation concerns the fact that ToM was assessed with a single video-based task, namely, the MASC. Other tasks of this type are available [see, for example, the Video Social Inference Task; (65,66)]. We selected this test because of its ecological validity, its ability to examine different subdomains of ToM as well as its high sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…However, the findings of this study also document a specific association between ToM performance and working memory processes (but not with flexibility and inhibition processes) as revealed by poorer ToM performance of sTBI patients than HCs in a condition with high demands on working memory processes. The association between working memory processes and ToM abilities in patients with sTBI and healthy controls was also investigated in a more recent study [ 56 ] by administering a ToM procedure (i.e., the Video Social Inference Test) in which the working memory load was manipulated. Results of this study showed that patients with sTBI performed worse than HCs on the ToM task; moreover, an association between working memory load and ToM performance was found in both experimental groups.…”
Section: Methodsmentioning
confidence: 99%